An ortho-quinone methide based strategy towards the rubromycin spiroketal family1. Issue 98 (23rd October 2015) - Willis, N. J.; Bray, C. D.
<x xml:space="preserve">Abstract</x> A method for the generation/in situ hetero-Diels–Alder cycloaddition of a trisubstituted ortho-quinone methide (o-QM) is described.